Effects of Acute Exposure to Polystyrene Nanoplastics on the Channel Catfish Larvae: Insights From Energy Metabolism and Transcriptomic Analysis - Jiang, Qichen; Chen, Xiaohui; Jiang, Hucheng; Wang, Minghua; Zhang, Tongqing; Zhang, Wenyi (Frontiers in Physiology, 2022)
Microplastics (nanoplastics) pollution has been a major ecological issue threatening global aquatic ecosystems. However, knowledge of the adverse effects of nanoplastics and the effects on freshwater ecosystems is still limited. To understand the impacts of nanoplastics on freshwater ecosystems, it is essential to reveal the physiological changes caused by nanoplastics in freshwater organisms, especially at their early life-history stages. In the present study, the larval channel catfish Ietalurus punetaus were exposed to gradient concentrations (0, 5, 10, 25 and 50 mg/L) of 75-nm polystyrene nanoplastics (PS-NPs) for 24 h or 48 h, and changes in contents of energy metabolites, metabolic enzyme activities and transcriptome were assessed. The results showed glucose and triglyceride contents increased after 24 h of exposure to 10 or 25 mg/L of PS-NPs but decreased with increased concentrations or prolonged exposure duration. Activities of most metabolic enzymes analyzed decreased in the larvae after 48 h of exposure, especially in 25 or 50 mg/L of PS-NPs. These suggested that PS-NPs caused huge energy consumption and disturbed the energy metabolism in larval fish. Transcriptomic analysis showed that 48 h of exposure to 50 mg/L PS-NPs impacted the expression of genes involved in protein digestion and induced response of proteasomes or heat shock proteins in the larval I. punetaus. The genes involved in peroxisome proliferator-activated receptors (PPAR) pathway and biosynthesis of amino acids were activated after the exposure. PS-NPs also depressed the expression of the genes involved in gonad development or muscle contraction in the larval I. punetaus. Overall, acute exposure to 75-nm PS-NPs disrupted the energy metabolism, consumed the energy reserves, and affected a series of molecular pathways which may further affect the development and survival of fish. This study provided the information about adverse effects of nanoplastics on the fish larvae and revealed the molecular pathways for the potential adverse outcomes.